Phytochemistry and Pharmacological Update on Tetraterpenoids - Kumari, Sapna; Goyal, Anju; Garg, Madhukar (Natural Products Journal, The, 2021)
Tetraterpenoids comprise of a large family of C 40 polyene, obtained from plants, fungi and bacteria. Their colouring properties have been employed to use as a natural colorant in the pharmaceutical industries. These exist as an attractive target of research because of their easy availability and plentiful health benefits in cardiovascular diseases, cancer, age related degenerative diseases, macular degeneration, antiatherosclerotic, anti-inflammatory, immunomodulatory properties and in HIV infection, probably due to their antioxidant properties. Formulating carotenoids in a particular dosage form is a big challenge as they possess some limitations like chemical unstability, poor bioavailability, less solubility and quick release. Due to this, numerous nanoencapsulation techniques have been developed till now to maintain their original properties. This review will highlight the phytochemical and pharmacological update on tetraterpenoids and their formulations.
Keywords: carotene